An Overview of Psychological Stress as a Cause of Tinnitus in Students of the Medical Education Program, Faculty of Medicine, Yarsi University, Class of 2023 and its Review from an Islamic Perspective - Nabilah Eka Saputri; Hastuti Rahmi; Muhammad Fazlurrahman Anshar; Aryenti Aryenti (Eduvest - Journal of Universal Studies, 2026)
Tinnitus, defined as the perception of sound without external auditory stimuli, is often associated with psychological stress, particularly among students facing high academic demands. This study aims to describe psychological distress as a contributing factor to tinnitus among medical students and to provide an overview from an Islamic perspective. A descriptive quantitative design with a cross-sectional approach was employed. The sample consisted of 84 students from the Medical Education Program, Faculty of Medicine, YARSI University, Class of 2023, selected using purposive sampling. Data were collected using the General Health Questionnaire-12 (GHQ-12) to measure psychological distress and the Tinnitus Handicap Inventory (THI) to assess tinnitus severity. Data analysis was conducted using univariate descriptive statistics with SPSS. The results show that the majority of respondents experienced positive psychological distress (89.3%), indicating relatively stable mental conditions, while 10.7% experienced negative distress. Regarding tinnitus, most respondents were in the none or very mild category (86.9%), with minimal impact on daily activities. These findings suggest that although psychological distress is present, tinnitus incidence remains generally low among students. In conclusion, psychological stress may contribute to tinnitus occurrence, but its severity is mostly mild, emphasizing the importance of stress management and maintaining psychological well-being